If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5c + -4b = 0 Reorder the terms: -4b + 5c = 0 Solving -4b + 5c = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-5c' to each side of the equation. -4b + 5c + -5c = 0 + -5c Combine like terms: 5c + -5c = 0 -4b + 0 = 0 + -5c -4b = 0 + -5c Remove the zero: -4b = -5c Divide each side by '-4'. b = 1.25c Simplifying b = 1.25c
| 4n+1-5n=6n+7-9n | | 4b+8=7b-4 | | -6f=-36 | | 3x-1=5x+7 | | 15a-10=20a | | (2/5)+x=(-1/10) | | -6(18+3y)=-9 | | (2n+2)(2n-2)= | | 14x-(10x-3)=17 | | (2/5)+=(-1/10) | | 13+(-15x)=74-12 | | (2n^2+2)(2n-2)= | | 2n+7n-28=26 | | 12x-5x=49 | | 12=3t | | 3xy+5x+2xy-8x= | | 14=2p | | 2/3(n-3)=1/3(n+6) | | 12(3x+4)-7=2x-23 | | ln(x)+ln(2)=3 | | -(-9x)=(-48) | | 5-4m-5m=m-4m+2 | | 6x-4y+x-5y= | | y=.5x-4 | | 14=2b | | y=-2.2x-5 | | 6x-8=2(x-4) | | 8xy-2xy= | | p+4-5=3p-8-7p | | 5x-8x+2x= | | (-6)-(2)-(-3)= | | 8q=38 |